American Dissertations on Foreign Education: A Bibliography with Abstracts. Volume XVII. Pacific: American Samoa, Fiji, Guam, Papua New Guinea, Ryukyu Islands, Solomon Islands, Tonga, Trust Territory of the Pacific Islands (Micronesia), Tubuai (French Polynesia), Western Samoa - Parker, Franklin, Ed; Parker, Betty June, Ed (The Whitston Publishing Company, 1986)
The editors attempt to examine and abstract all locatable doctoral dissertations completed in the United States, Canada, and some European countries that pertain to the Pacific area. Specifically, these dissertations deal with American Samoa, Fiji, Guam, Papua New Guinea, Ryukyu Islands, Solomon Islands, Tonga, Trust Territory of the Pacific Islands (Micronesia), Tubuai (French Polynesia), and Western Samoa. The dissertations focus significantly on public and private education at all school levels and on all school subjects. They deal with the work and influence of educational, scientific, and cultural agencies, individuals, and movements. Some dissertations which deal only marginally with education and learning are included when they seem to be of special relevance. (BZ)